Rezonans medialny nowelizacji ustawy o Instytucie Pamięci Narodowej w wybranych tygodnikach opinii - Zemła, Bernardyna (Polityka i Społeczeństwo, 2020)
In the prelude I introduce threads related to European anti-Semitism. Presenting the functionalists’ standpoint, I elaborate on contemporary attempts to explain the phenomena of mass murder of the Jewish nation during World War II, while placing emphasis on the fact that the historical politics of the Holocaust in Israel and Poland is not yet a closed chapter. Following these conclusions, the goal and methodology of my research is devoted to media reaction to the amendment to the Act pertaining to the Institute of National Remembrance in chosen Polish weekly newspapers of record. In the end I present the results of the research conducted from 29th of January to 15th of April.